THE LAO PEOPLE’S DEMOCRATIC REPUBLIC AND SUSTAINABLE DEVELOPMENT GOAL 18: : LIVES SAVE FROM UXO (UNEXPLODED ORDNANCE) - Sinta Herindrasti (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
The Sustainable Development Goals is a global agenda of the United Nations to cope with global challenges that is formulated into 17 goals including its indicators. The Lao PDR as part of global society and member of the United Nations commits to implement the SDGs but with one additional conditional goal that is SDG 18 Lives save from UXO (Unexploded Ordnance). SDG 18 as part of response toward local challenge reminds the war’s impact which threatening peoples’ live all at once the urgent need to solve the problem completely for achieving other 17 goals. How is Lao struggling the Goal 18 through various form of cooperations and partnerships become the precious part in the process of documenting the best practices of achieving SDG 18. This article want to explore various initiatives of the Lao government and its implementation with international partners’ support. Target formulation is a positive initial step while the successfulness to fulfill the target is something that must be conducted continously Key words: Sustainable Development Goals, Lives Save from Unexploded Ordnance (UXO), Partnership, Peace